The indonesian grammatical interference on EFL students’ writing - Ayu Rizki Septiana (Universitas Islam Malang, 2020)
This research was aimed to find out what factors of the occurrence of Indonesian grammar interference in EFL students’ writing and what type of Indonesian grammar interference occur in EFL students’ writing. To answer the research problem on Indonesian grammatical interference, a descriptive qualitative was done by taking the fourth semester students of English Department STKIP PGRI Tulungagung as the subject of the research. Further, the data related to the Indonesian grammar interference were taken using test and observation. The result of data analysis shows that the students still got interference from Indonesian grammar as their native language. The grammatical interference in this research is classified into two; syntactical interference and morphological interference. The syntactical interference consists of word order, preposition, extra word and missing word. The most interference in syntactical interference is on preposition. The morphological interference consists of omission of determiner, wrong determiner, subject-verb agreement, be form, tenses usage, singular and plural form. The most interference in morphological interference is omission of determiner. From the observation, it was found that the cause of interference is the different structure of Indonesian and English grammar. Moreover, the students usually wrote it first in Indonesian and later translated into English.